Radial Basis Point Interpolation Method with Reordering Gauss Domains for 2D Plane Problems - Shi-Chao Yi; Fu-jun Chen; Lin-Quan Yao (Journal of Applied Mathematics)
We present novel Gauss integration schemes with radial basis point interpolation method (RPIM). These techniques define new Gauss integration scheme, researching Gauss points (RGD), and reconstructing Gauss domain (RGD), respectively. The developments lead to a curtailment of the elapsed CPU time without loss of the accuracy. Numerical results show that the schemes reduce the computational time to 25% or less in general.